FOUR SQUARE WRITING METHOD (FSWM) USED IN PROCESS APPROACH TO TEACHING WRITING OF ANALYTICAL EXPOSITION TEXTS - Ullah, Wa Ode Ritna Yuniyr (2015)
This study aims to investigate the ways FSWM helps students write analytical exposition texts as well as the students' attitude towards the use of FSWM in teaching analytical exposition texts. This study mainly utilizes a qualitative research design covering the trait of a case study. This study was carried out at one private senior high school in Bandung involving one class from the second grade students. The data were collected through classroom observation, collection of students' texts, questionnaires, and interview. The data from clasroom observation, students' texts, and interview were analyzed qualitatively while the data from the questionnaires were analyzed quantitavely (through frequency, mean, and percentage). This study reveals two main findings related to the research questions. First, from classroom observation and students' texts, it was found that through the steps found in FSWM students showed significant improvement in their writing skill particularly in social function, schematic structure, and the language features. In addition, the observed steps found in FSWM did help students to write systematic, cohesive and coherent texts. Furthermore, the result of the questionnaires and interview revealed that students held positive attitude in writing analytical exposition text using FSWM. Accordingly, it is recommended that this method be implemented in the teaching of writing particularly to senior high school students.